Exploring ICT competency and communication preferences in higher education: insights from Croatia - Budić, Hrvoje; Šostar, Marko; Ryngelblum, Arnaldo (Institute of Advanced Engineering and Science, 2025)
The digital transformation of education underscores the need for effective integration of information and communication technologies (ICT) in higher education. This study examines differences in ICT usage between teaching staff and students across various types of higher education institutions in Croatia, focusing on the impact of institution type and academic programs on ICT usage levels, digital competencies, and communication preferences. A quantitative research approach was employed, with data collected via a survey distributed to 70 teaching staff and 472 students using random sampling from public universities, public polytechnics, and private higher education institutions. The results reveal significant disparities in digital competencies, with students in private institutions demonstrating higher ICT usage compared to public institutions. Additionally, both groups favor synchronous communication (SC), although students display a stronger preference. These findings highlight a digital divide within academia and the need for targeted ICT training, particularly in public institutions. The study proposes measures to enhance ICT infrastructure and develop digital competencies through systematic workshops and training sessions. This research emphasizes the importance of addressing digital inequalities and improving the quality of education by integrating advanced technological solutions in higher education.